Generative AI in Higher Education: Opportunities, Ethical Challenges, and Responsible Integration - Wouroud ElFarmawi (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2026)
The rapid advancement of generative artificial intelligence (GenAI) has significantly transformed educational practices, particularly through the emergence of large language models (LLMs) such as ChatGPT, Google Gemini, Claude, and Microsoft Copilot. These technologies present substantial opportunities for enhancing teaching, learning, assessment, and academic support while simultaneously raising ethical, pedagogical, and governance-related concerns. This study presents a PRISMA-informed systematic review of the literature examining the applications, benefits, challenges, and ethical implications of generative AI in higher education. Peer-reviewed studies published between 2018 and 2025 were identified and analyzed using a structured review methodology, with particular emphasis on research published after 2022 following the widespread adoption of generative AI tools in educational settings. The findings revealed four major themes: pedagogical applications of generative AI, educational benefits and learning opportunities, ethical challenges and academic risks, and institutional governance for responsible AI integration. The review indicates that generative AI supports personalized learning, instructional design, academic writing assistance, language learning, and student engagement through adaptive and interactive educational experiences. However, the literature also identifies significant concerns related to academic integrity, algorithmic bias, misinformation, overreliance on AI-generated content, data privacy, and inequitable access to emerging technologies. The findings further highlight the growing need for institutional policies, AI literacy initiatives, faculty training, and ethical governance frameworks to support the responsible integration of generative AI in education. This review contributes to the evolving discourse on artificial intelligence in higher education by synthesizing current evidence, identifying key research gaps, and proposing a framework for responsible AI integration. The study emphasizes that the effective adoption of generative AI requires balancing technological innovation with ethical accountability, transparency, academic integrity, and educational equity.